Pemetaan Daerah Di Kabupaten Landak Berdasarkan Tingkat Kekeringan Berbasis Penginderaan Jauh - Selvia, Siska Ita; Taufiqurrahman; M. Irvan Kurnia; Siddiqirly, Muhammad (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2024)
The drought conditions in Landak Regency are meteorological droughts caused by a decrease in rainfall intensity. This results in a need for more water supply to meet the community's clean water needs. To reduce the widespread impact of this drought disaster, this research aims to conduct a spatial study to provide information for making decisions in handling drought. The method used in this research is the Normalized Difference Drought Index (NDDI), which combines the values of the Normalized Difference Vegetation Index (NDVI) and the Normalized Difference Water Index (NDWI). This research shows that Landak Regency is classified as moderately dry with a score range of 0.31-0.65 with a total area of 770,493.25 ha. Meanwhile, a high level of drought with a score of >1 covers an area of 17,881.11 ha. Districts with high levels of drought are concentrated in Ngabang and Mandor Districts. These two sub-districts are the centre of economic growth in Landak Regency, with the highest population density.